THE ENLIGHTENED-SHAREHOLDER-VALUE APPROACH VERSUS PLURISM IN THE MANAGEMENT OF COMPANIES - Irene-marie Esser (Obiter, 2022)
Social, safety, health and environmental factors have recently been reconsidered in the managing of a company. The so-called triple bottom line is the buzzphrase, embracing not only financial performance but also social and environmental responsibility of companies (Crook “The Good Company” January 2005 The Economist 1-18; and Freemantle and Rockey The Good Corporate Citizen (2004) 7). Executive and non-executive directors are the people responsible for monitoring and controlling companies. The issue is, however, in whose interests this should be done? (Havenga Fiduciary Duties of Company Directors with Specific Regard to Corporate Opportunities (1998) 1; Mongalo “The Emergence of Corporate Governance as a Fundamental Research Topic in South Africa” 2003 SALJ 176-177, and generally Du Plessis “Direkteure se Pligte Teenoor Partye Anders as die Maatskappy” 1992 De Jure 378-392). The generally accepted viewpoint is that the paramount fiduciary duty of directors, individually and collectively, is to exercise their powers in good faith and in the best interest of the company as a whole (see generally Du Plessis 1992 De Jure 378-392; Havenga “The Company, the Constitution, and the Stakeholders” 1997 Juta Business Law Journal 134, 136; and Sealy “Directors‟ „Wider‟ Responsibilities – Problems Conceptual, Practical and Procedural” 1989 Monash University Law Review 164-188). This note focuses on arguments for and against exclusive shareholder protection. The current company law reform process in South Africa and the recent reform process in the United Kingdom are discussed and evaluated. The consideration of matters affecting stakeholders and whether they are subordinate to that of the directors’ primary goal to promote the success of the company in the best interest of the shareholders is discussed.